Akuzipik/Yupik (St. Lawrence Island, Alaska, USA; Chukotka, Russia) Language Snapshot. (2021) - KOONOOKA, CHRISTOPHER PETUWAQ; SCHREINER, SYLVIA L.R.; SOLDATI, GIULIA MASELLA; SCHWARTZ, LANE; HUNT, BENJAMIN; HAAS, PRESTON
No abstract available